ISRE-Reporter Mouse Reveals High Basal and Induced Type I IFN Responses in Inflammatory Monocytes - Melissa B. Uccellini; Adolfo García-Sastre (Cell Reports, 2018)
Summary: Type I and type III interferons (IFNs) are critical for controlling viral infections. However, the precise dynamics of the IFN response have been difficult to define in vivo. Signaling through type I IFN receptors leads to interferon-stimulated response element (ISRE)-dependent gene expression and an antiviral state. As an alternative to tracking IFN, we used an ISRE-dependent reporter mouse to define the cell types, localization, and kinetics of IFN responding cells during influenza virus infection. We find that measurable IFN responses are largely limited to hematopoietic cells, which show a high sensitivity to IFN. Inflammatory monocytes display high basal IFN responses, which are enhanced upon infection and correlate with infection of these cells. We find that inflammatory monocyte development is independent of IFN signaling; however, IFN is critical for chemokine production and recruitment following infection. The data reveal a role for inflammatory monocytes in both basal IFN responses and responses to infection. : Uccellini and García-Sastre create an ISRE reporter mouse and track interferon (IFN) responses in vivo in response to pathogen-associated molecular pattern (PAMP) stimulation and influenza infection. They find that IFN responses are highest in hematopoietic cells during infection. Specifically, Ly6Chi inflammatory monocytes have high basal IFN responses that are further enhanced upon infection. Keywords: influenza, interferon, monocytes, innate immunity